PELAKSANAAN ELEKTRONIK SYSTEM (E-SYSTEM) DAN AKUNTANSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN - Budi Harto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2016)
ABSTRACT : Economic development is directed at efforts to achieve economy of an independent and viable state to improve the welfare of the entire territory of Indonesia in a fair and equitable. Thus economic growth should be directed to increase the income of Indonesia, in the economic crisis while the wheels of government and development may not be driven without the financial support comes primarily from domestic revenues. Therefore, the government tried to constantly enhance the role of sources of state revenue, especially revenue from non-oil exports. Proceeds from this non-oil part will be improved through taxation revenue. The main mission of the Directorate General of Taxation is the mission of the fiscal tax revenue by collecting tax law that can support the independence of government funding and are carried out effectively and efficiently (Suryadi, 2006). To achieve the target of the tax, have grown continuous public awareness and compliance of taxpayers to fulfill tax obligations in accordance with applicable regulations. Given the awareness and taxpayer compliance is an important factor for the increase in tax revenue, it needs to be studied intensivelyabout the factors that influence taxpayer compliance, particularly corporate taxpayers.